Intercropping of corn (Zea mays L.) with groundnut (Arachis hypogea L.) and bambara nut (Vigna subterranea L.) to increase protein content of combined forage - Belel, Dauda Mustapha (2016)
Forage corn has been used as a feed resource for ruminant but it is low in crude protein content such that animals have to be supplemented with protein sources. In order to increase the protein in corn forages, three corn intercropping experiments were conducted with two grain legumes: bambara nut (Vigna subterranea L. Verdc) and groundnut (Arachis hypogea L.) to evaluate their potential to increase forage quality. In the first experiment, six introduced bambara nut landraces from Nigeria (Bambwus, Kurvu, KwadaZwalang, Tanyanyi, IndaraAyaghayagha and Karamagdanda) and one from Thailand (Songkla 1) were evaluated. The Songkla 1 variety has been grown in Malaysia over the last 15 years while the Nigerian landraces are newly introduced. The objective was to evaluate whether the Nigerian landraces could perform as well or better than the Songkla 1 variety in the Malaysian environment. There were significant differences (p<0.05) among the introduced African landraces and the adapted Songkla 1 variety. Kurvu recorded a higher forage dry matter (2,343 kg ha-1) and pod yield (1,349 kg ha-1). Harvest index was higher at 46.8% for Bambwus. In general, the introduced African landraces showed a better performance than the adapted Songkla1 variety and hence some of these landraces could be selected for planting in the tropical humid climate of Malaysia. Bambwus was superior to other varieties and was ranked first and was selected for inclusion in the subsequent corn/legume intercropping experiments. In the second experiment, corn was intercropped with bambara nut and groundnut at a 1:1 ratio to determine the contribution of each legume towards the yield and quality of the combined forage. The experiment involved six treatments (sole corn with nitrogen, sole corn without nitrogen, sole groundnut, sole bambara nut, corn/bambara nut intercrop and corn/groundnut intercrop) replicated three times in a randomized complete block design. Nitrogen fertilizer was not applied to all treatments except for the first treatment. Intercropping significantly (p< 0.05) increased the growth of corn crop and suppressed both bambara nut and groundnut. A higher yield was obtained from nitrogen-fertilized corn. However, intercropping showed its advantage through 36% and 59% better land equivalent ratio (LER) in intercrop than in monocrop for corn/bambara nut and corn/groundnut respectively. The relationship between corn and the legumes was synergistic in nature as shown by relative yield total which was 1.36 for corn-bambara nut and 1.59 for corngroundnut. Digestibility was higher in the corn/legume forage (57.5%) compared to sole corn (51.8%). Similarly, corn intercropped with bambara nut and groundnut had higher protein content (10.8 and 12.9%) compared to sole corn (8.21%). Groundnut was a better legume for intercropping with corn than bambara nut in terms of yield but bambara nut was selected for the next study in order to further understand its performance in humid tropical environment. In the third experiment, corn was intercropped with bambara nut landrace Bambwus in a randomized complete block design using different planting patterns based on the ratio of corn/bambara nut as follows (C=Corn, B=Bambara, N=Nitrogen):C4:B0, C4:B0+N, C3:B1, C2:B2, C1:B3, C0:B4. The crop growth rate, leaf chlorophyll and total leaf area were significantly higher among the intercrops compared to monocrops. Total dry matter yield was similar in all combinations. Sole corn had 73% neutral detergent fiber (NDF) which was higher than in the intercrops except C1:B3. Corn/bambara nut combinations ratios also differed significantly in NDF and acid detergent fiber (ADF). Protein in sole bambara nut was 14.8%. Among the combinations, crude protein was highest in C1:B3 (17.3%). Crude protein in sole corn was 8.52%. Lignin was highest in combinations with more bambara nut with sole bambara nut having 4.92% lignin. The planting patterns all gave a land equivalent ratio (LER) higher than 1.00 which indicated the benefit of intercropping. Aggressivity index indicates that corn was more aggressive than bambara nut in their competition. For improvement of overall forage quality it is recommended that bambara nut be planted as an intercrop with corn at the ratio of 1 corn to 3 bambara nut. The Nigerian landrace Bambwus should be used in place of Songkla 1 because of its relatively superior performance.